How to Help Young Children Ask Better Questions? - Ruggeri, Azzurra; Walker, Caren M.; Lombrozo, Tania; Gopnik, Alison (Frontiers in Psychology, 2021)
In this paper, we investigate the informativeness of 4- to 6-year-old (N = 125) children’s questions using a combined qualitative and quantitative approach. To do so, children were presented with a hierarchical version of the 20-questions game, in which they were given an array of objects that could be organized into three category levels based on shared features. We then tested whether it would be possible to scaffold children’s question-asking abilities without extensive training. In particular, we supported children’s categorization performance by labeling the object features needed to ask effective constraint-seeking questions. We found that with both age and scaffolding children asked more effective questions, targeting higher category levels and therefore reaching the solution with fewer questions. We discuss the practical and theoretical implications of these results.